Detection of Theileria equi infection in ixodid ticks of equines using nested polymerase chain reaction from Punjab, India - SUMBRIA, DEEPAK; SINGLA, L D; SHARMA, AMRITA; BAL, M S (The Indian Journal of Animal Sciences, 2018)
The aim of this study was to perceive Theileria equi DNA in ticks by nested PCR and to list the risk factors associated with infection in equines from Punjab. A total of 84 ticks were obtained from 464 screened animals. The local tick variety was identified and verified on the basis of characters revealed in scanning electron microscopy. Amplicons of 665 bp obtained by nPCR specific for 18S rRNA of T. equi were detected in 13.1% of ticks, with higher risk of infection in western than in eastern Punjab. Incidence of parasite was higher in Hyalomma anatolicum anatolicum as compared to Rhipicephalus (Boophilus) microplus, particularly the female ticks. Phylogenetic analyses indicated closed homology with strain from Brazil. This is the first study of T. equi incidence in ixodid ticks in Punjab which is the most important vector for the spread of the infection to healthy equine in endemic areas.